LEKSIKON BUDAYA DALAM TRADISI ANTAR AJONG PADA MASYARAKAT MELAYU SAMBAS - Kurnia, Sri; Saman, Sisilya; Syahran, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe antar ajong tradition found in Sambas Malay society is one among the richness of the Sambas community in a culture. The purpose of cultural lexicon research in inter ajong tradition is to know the form, the lexical meaning, the cultural meaning, and the supplement of the text of Indonesian language learning Curriculum 2013. The method used in this research is descriptive method and using ethnolinguistic approach. Sources of data studied in the form of speech from informants containing cultural lexicon contained in antar ajong tradition in the form of words and phrases. Techniques used in this study, namely interviews, proficient, and record. Data collection tool in the form of recorder, camera, and stationery. Based on the research conducted, the data collected was gathered by 106 cultural lexicons in antar ajong tradition in Sambas Malay society. Cultural lexicon in inter ajong tradition in this research consists of three forms, the word in the form of monomorfemis and polymorphism and phrase. The lingual unit of monomorphism is 80 words. The lingual unit in the form of polymorphism is 7 words. The lingual unit of the phrase is 25 words. The term has a lexical meaning totaling 82 words and which has a cultural meaning amounting to 106, while the cultural meaning in the form of spells is 4, prohibited abstinence is 7, oral literature and cultural lexicon data contained in the tradition of antar ajong total 106. Â Keywords: lexicon, antar ajong tradition, Malay SambasÂ